2017
DOI: 10.22354/in.v21i2.651
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of Shiga toxin-producing escherichia coli isolates from human and sheep in Al-Madinah Al-Munawarah

Abstract: Shiga toxin-producing Escherichia coli (STEC) strains have emerged as important foodborne pathogens of global public health concern, causing life-threatening diseases. Sheep and their products have been documented as important reservoirs for STECs, especially E. coli O157. The aim of this study was to investigate STECs from diarrheal human and sheep in Al-Madinah Al-Munawarah, Saudi Arabia. Fecal samples were collected between June and August, 2015 from diarrheal humans (n = 134) and sheep (n = 87). Presumptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The absence of the stx genes in this study may be attributed to the loss of the stx-phages during storage as stx genes are temperate phage-mediated that may be lost from the bacterial genome (Karch et al, 1992;Lawan et al, 2015). The presence of eaeA and hlyA gene in the study is in agreement with the report of previous studies (Sharaf and Shabana, 2016;Fashina et al, 2018). The presence of the eaeA and hlyA gene in this study is of public health importance as these genes could confer enhanced virulence during infection.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of the stx genes in this study may be attributed to the loss of the stx-phages during storage as stx genes are temperate phage-mediated that may be lost from the bacterial genome (Karch et al, 1992;Lawan et al, 2015). The presence of eaeA and hlyA gene in the study is in agreement with the report of previous studies (Sharaf and Shabana, 2016;Fashina et al, 2018). The presence of the eaeA and hlyA gene in this study is of public health importance as these genes could confer enhanced virulence during infection.…”
Section: Discussionsupporting
confidence: 92%
“…For carbapenem-resistant P. aeruginosa isolated from patients, 4.1-18.4% carried blaVIM and 4.7-21.0% carried blaIMP [39,42,43]. Shiga toxin-producing E. coli among diarrheal isolates showed 70% resistance to trimethoprim-sulfamethoxazole [44]. A number of studies showed different extended-spectrum-β-lactamase (bla) genes that had been identified in the Hajj [23,[35][36][37]45,46] (Table 1).…”
Section: Antimicrobial-resistant Bacteria Among Enterobacteriaceaementioning
confidence: 99%
“…Most of these isolates have at least two or three gene arrangements, and only four isolates show a combination of four genes with profiles of stx1, stx2, hlyA, and afaI. However, many researchers have attempted to correlate the existence of recognized virulence profile factors with a disease or severity of a disease and concluded that no single factor is responsible for the virulence of STEC [46][47][48]. These variations in gene virulence and severity may contribute to the overuse and misuse of antibiotics in intensive animal production as well as in the crowded and stressful conditions of factory farms.…”
Section: E Coli Isolation (%)mentioning
confidence: 99%